Integrating Maslow’s Self-Actualization Theory with Qur’an and Hadith: A Framework for Holistic Growth of Islamic Education Students - Khurriyyah, Liza Jauharotul Munfarida Al; Sabarudin, Sabarudin; Sukran, Ahmad (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2026)
This study aims to integrate Abraham Maslow's concept of self-actualization with the perspectives of the Qur'an and Hadith in the context of student development. The method used is qualitative research, employing a library-based approach and content analysis of Maslow's works. The results show that Maslow's theory of self-actualization recognizes the dimensions of value and peak experience, but in modern educational practice, it is often reduced to individualistic and secular. Integration with the Qur'an and Hadith expands the meaning of self-actualization into a process of developing fitrah oriented towards monotheism, responsibility ('ubudiyyah), moral development, and social responsibility. Self-actualization in the Islamic perspective does not stop at personal achievements but is directed toward the formation of knowledgeable, moral, and beneficial people who benefit others. This conceptual reconstruction offers an integralistic educational paradigm that unites psychological, spiritual, and social dimensions in the process of student growth and development. The main contribution of this article lies in the attempt at a conceptual synthesis between Western humanistic psychological theories and Islamic educational values that resulted in a new theoretical framework of monotheism-based self-actualization. In addition, this article provides an epistemological foundation for the development of a more holistic educational model, as well as an academic reference for educators and researchers in designing learning strategies that are not only oriented towards cognitive achievement, but also on the formation of students' character, spirituality, and social responsibility.